Comparison of the Spectrum of Local Treatment Sequelae in Breast Cancer Patients Undergoing Modified Radical Mastectomy versus Breast-Conserving Surgery with Adjuvant Radiation Therapy - Kale, Niraj Satish (Journal of Biomedical and Pharmaceutical Research, 2014)
Background: Breast cancer is the most common malignancy affecting women globally. Treatment options such as Modified Radical Mastectomy (MRM) and Breast-Conserving Surgery (BCS) with adjuvant radiation therapy offer distinct advantages. However, both modalities have varying post-treatment sequelae, including lymphedema, pain, and reduced quality of life. Identifying these differences is critical to guide clinical decisions.Objective: To compare the local treatment sequelae between patients undergoing MRM versus BCS with adjuvant radiation therapy.Material and Methods: This observational study included 120 patients with breast cancer—60 treated with MRM and 60 with BCS followed by radiation therapy. Patients were followed for six months post-treatment. Inclusion criteria were patients aged 30–70 years with early or locally advanced breast cancer. Exclusion criteria included metastatic disease and previous breast surgery.Results: Patients undergoing MRM experienced higher rates of lymphedema (30%) compared to those with BCS (10%). Pain scores were also higher in the MRM group. However, radiation-related complications were observed in 25% of the BCS group.Conclusion: Both MRM and BCS followed by radiation have distinct sequelae. MRM patients showed higher rates of lymphedema and pain, while BCS patients were prone to radiation-related side effects. Clinical decisions should consider these outcomes to optimize care.Keywords: Breast cancer, Modified Radical Mastectomy, Breast-Conserving Surgery, Adjuvant radiation therapy, Treatment sequelae, Lymphedema.